Associations of Domain‐Specific Physical Activity With Mental Health Symptoms Among Finnish Employed Adults: A Population‐Based Study - Jussila, Juuso J.; Pulakka, Anna; Appelqvist‐Schmidlechner, Kaija; Halonen, Jaana I.; Ervasti, Jenni; Salo, Paula; Lahti, Jouni; Mikkonen, Santtu; Lanki, Timo (Wiley, 2026)
Leisure-time physical activity has consistently been associated with better mental health. However, evidence on active commuting and occupational physical activity is less conclusive. We examined cross-sectional associations of domain-specific physical activity with depressive symptoms and psychological distress among Finnish employed adults. We included 3439 adults (mean age 45.0 years; 51% female) from the FinHealth 2017 Study. Based on commuting, occupational and leisure-time physical activity behaviour, participants were categorised as passive or active commuters; sedentary, lightly active or moderately/highly active workers; and sedentary, recreationally active or exercisers/athletes, respectively. Daily active commuting volumes were also assessed. Logistic regression was used to estimate odds ratios, with models adjusted for key covariates. High volumes of active commuting (≥ 30 min a day) were associated with higher odds of depressive symptoms (OR 1.58, 95% CI 1.18–2.13), whereas no associations were observed for lower active commuting volumes or when active commuting was analysed as a binary variable. Regarding occupational physical activity, lightly active workers were less likely to experience psychological distress (OR 0.62, 95% CI 0.40–0.97) compared to sedentary workers, whereas no associations were observed for moderately or highly active workers. Regarding leisure-time physical activity, exercisers and athletes had lower odds of depressive symptoms (OR 0.44, 95% CI 0.32–0.61) and psychological distress (OR 0.34, 95% CI 0.21–0.55) compared to sedentary individuals, as did recreationally active adults. Leisure-time and light occupational physical activity, but not active commuting, were associated with fewer mental health symptoms. Potential mental health benefits of physical activity may be domain- and volume-specific.